Family theraphy - Sealey, Francis; Stevens, Richard ([S.l.] : Open University Educational Enterprises, 1981)
The programme is intended to demonstrate an application of psychology in a clinical context which may be considered within the humanistic perspectives, and personal construct theory
Copy available in DVD format
Keywords: Psychotherapy